1269: Submission of the Muslims of Southern Italy to Charles I of Anjou (Transmediterranean History, 2021)
This article uses Latin sources to show how the Muslims living in southern Italy were able to make peace in 1269 with their new king, Charles of Anjou, against whom they had rebelled out of loyalty to the previously ruling Staufen dynasty. Correcting assumptions formulated in previous research, the article argues that a form of settlement was achieved on the basis of a particular ritual of subjection that was accepted by both Christian and Muslim subjects. Whereas the Muslims' situation deteriorated militarily and financially, they retained the right to practise their religion under royal protection. In consequence, their submission did not foreshadow the enslavement of the Muslims of southern Italy in 1300. In 1269, religious pragmatism still prevailed.
Keywords: conquest; deportation; dhimma; Hohenstaufen Dynasty; Lucera; rebellion